Australian medical radiation science graduates’ experiences of resilience during transition to professional practice - Maresse, Sharon (Curtin University, 2014)
Health professionals experience adversity as they make the transition from student to independent practice. Resilience during transition to practice for the medical radiation sciences (MRS) is unexamined. A grounded-theory approach was used to explore resilience among new Australian MRS professionals, resulting in a theoretical conceptualisation of resilience as a process of evolution, with phases of impact, energising, maintaining momentum, achieving equilibrium, and beating inertia. Resilience can be fostered by educators, colleagues, employers and professional organisations.